1997
DOI: 10.1046/j.1469-8137.1997.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of fructan in grasses: a β‐(2‐6)‐linkage specific fructan‐β‐fructosidase from stubble of Lolium perenne

Abstract: SUMMARYSeveral different fructan and sucrose hydrolysing enzyme activities were induced in roots and stubble (mainly leaf sheaths) of Lolium perenne L. plants after defoliation. Among those activities, a fructan-/?-fructosidase (EC 3 .2.1.80) that hydrolyses predominantly /?-(2-6)-fructosyl-fructose linkages (6-FEH) was purified from the stubble. The use of the substrate 6,6-kestotetraose and high-performance anion-exchange chromatography with pulsed amperometric detection allowed linkage-specific screening an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 50 publications
3
41
1
2
Order By: Relevance
“…Both 1-FEHs had optimal activities between 30°C and 40°C, but activities remained surprisingly high at the lower temperature range (not shown). Similar properties were observed for a 1-FEH from barley (Henson, 1989) and a 6-FEH from ryegrass (Marx et al, 1997b).…”
Section: Enzymatic Propertiessupporting
confidence: 65%
See 2 more Smart Citations
“…Both 1-FEHs had optimal activities between 30°C and 40°C, but activities remained surprisingly high at the lower temperature range (not shown). Similar properties were observed for a 1-FEH from barley (Henson, 1989) and a 6-FEH from ryegrass (Marx et al, 1997b).…”
Section: Enzymatic Propertiessupporting
confidence: 65%
“…Also, 6-FEH and invertase activities were present in crude extracts, but they eluted in different fractions. As observed for most other plant FEH enzymes Marx et al, 1997aMarx et al, , 1997bDe Roover et al, 1999), the final 1-FEH w1 and w2 preparations showed negligible invertase activity (Table II). In severe contrast to plant FEHs, which are only capable of degrading fructans and not Suc, ␤-fructo(furano)sidases (EC 3.2.1.80) can degrade Suc as well as fructans.…”
Section: Properties Of Plant Fehsmentioning
confidence: 72%
See 1 more Smart Citation
“…In fungi, inulin can be degraded endolytically by inulinases (Uchiyama, 1993) as well; however, in plants, only (exo)-fructan-/5-fructosidases have been identified up to now (Edelman & Jefford, 1964;Rutherford & Deacon, 1972;Yamamoto & Mino, 1985;Wagner & Wiemken, 1986;Henson, 1989;Claessens et al, 1990;Simpson et al, 1991;Bonnett & Simpson, 1995;Henson & Livingston, 1996;Marx et al, 1997). Generally, two different mechanisms of exolytic degradation of sugar oligomers and polymers are kinetically distinguishable.…”
Section: Properties Of 1-fehmentioning
confidence: 99%
“…In the present and the companion paper (Marx, Nosberger & Frehner, 1997), we focus on the processes of fructan degradation in plants. We have identified FEH activities from different plant species and have determined their physiological relevance to fructan degradation in planta.…”
Section: Introductionmentioning
confidence: 99%